Datazioni U-Pb SU Zirconi nei sedimenti post massimo glaciale del mare di Ross (Antartide) - Loregian, Diana (2022)
Reconstruction of the dynamics of polar ice sheets is very important for climate modelling. In this work, I tried to obtain some information about the ice flow across the Ross Sea (Antarctica) through sedimentary provenance analysis. Samples have been collected from seven cores drilled in the past years. Sediments were processed through chemical and magnetic separation in order to obtain a sufficient amount of zircons. These grains have been analyzed first at a cathodoluminescence microscope and then with the U-Pb method at the ICP-MS lab of CNR-IGG in Pavia. Data show that samples from the eastern sites of the bay contain a main population of Cretaceous zircons (100-110 Ma) which are much rarer in the western locations. Here, most of the grains are between 500 and 550 Ma, which are the ages most common in the crystalline basement of Transantarctic Mountains. Finally, these data allowed to distinguish the sediments related to the West Antarctic Ice Sheet from those deriving from the East Antarctic Ice Sheet. open